Chloroplast fructose-1,6-bisphosphatase: the product of a mosaic gene. - Raines, C A (1988)
We show here that light stimulates the expression of nuclear genes in wheat leaves for chloroplast fructose-1,6-bisphosphatase (FBPase) and describe a sequence of amino acids in this enzyme which may be responsible, via thioredoxin, for the light regulation of its activity. This data results from (a) our isolation and characterization of a cDNA of this enzyme which contains its entire coding sequence, and (b) our use of this cDNA as a probe to detect mRNA levels in wheat plants subjected to different light regimes. The similarity in amino acid sequence of the encoded enzyme from diverse sources suggests that the FBPase genes all had a common origin. However, their control sequences have been adjusted so that they are appropriately expressed and their coding sequences modified so that the enzymic activity of their products are suitably regulated in the particular cellular environment in which they must function. The light-activated regulatory sequences in the gene for the chloroplast protein have probably come together by a shuffling of DNA segments.